(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Civil engineering structures have been adversely affected by dynamic effects from past to present. This has always been a problem for civil engineering. Civil engineers strive to design structures to be least affected by dynamic effects. The biggest challenge in these designs is the exact and realistic calculation of the effect of dynamic effects on the structure. There are various methods for calculating the dynamic effects affecting the structures. System identification method is one of the methods used to calculate the responses of the building to the dynamic effects affecting the buildings.